2023
DOI: 10.3390/plants12040902
|View full text |Cite
|
Sign up to set email alerts
|

Ferula sinkiangensis (Chou-AWei, Chinese Ferula): Traditional Uses, Phytoconstituents, Biosynthesis, and Pharmacological Activities

Abstract: Ferula is the third largest genus of the Apiaceae family, its species are utilized as a remedy for diverse ailments all over the world. F. sinkiangensis K. M. Shen (Chou-AWei, Chinese Ferula) is mainly found in Xin-jiang Uygur Autonomous Region, China. Traditionally, it is utilized for treating various illnesses such as digestive disorders, rheumatoid arthritis, wound infection, baldness, bronchitis, ovarian cysts, intestinal worms, diarrhea, malaria, abdominal mass, cold, measles, and bronchitis. It can produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…A group of lignans consisting of 120 structures was collected from a previous publication [ 30 , 31 ] and also subjected to energy minimization using the OPLS4 force field, utilizing the MacroModel tool in Maestro [ 60 ] with the PRCG (Polac–Ribiere conjugate gradient) method (2500 iterations). For upcoming studies, the conformation with the lowest energy for each compound was chosen.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A group of lignans consisting of 120 structures was collected from a previous publication [ 30 , 31 ] and also subjected to energy minimization using the OPLS4 force field, utilizing the MacroModel tool in Maestro [ 60 ] with the PRCG (Polac–Ribiere conjugate gradient) method (2500 iterations). For upcoming studies, the conformation with the lowest energy for each compound was chosen.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, various studies explored the biological potential and possible action mechanisms by which lignans exert their anticancer effectiveness. In this regard, the reported lignans from Ferula sinkiangensis and Justicia procumbens [ 30 , 31 ] ( Supplementary Table S1 ) were assessed as valuable sources for the development of novel anticancer therapeutics [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gambogic acid, one of the active components of resin, was approved for clinical trials as a class 1 new drug in 2004 by the Chinese Food and Drug Administration [ 1 ]. Continuous investigations revealed that many plants can produce a diverse array of bioactive compounds, some of which are also used as drugs, such as paclitaxel, morphine, ephedrine, and ferulic acid [ 4 , 5 , 6 ]. Inspired by these exciting works, more and more natural product researchers [ 7 ] and synthetic chemists [ 8 ] have shown great interest in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Ferula , the third largest genus in the family Apiaceae, is distributed worldwide, particularly in Asia ( Khayat et al., 2023 ) ( Supplementary Figure 1 ). Ferula is a perennial herb that bears one or more fruits.…”
Section: Introductionmentioning
confidence: 99%